Literature review: Complementary and Alternative Medicine in Serbia - Luketina-Šunjka, Marina; Rančić, Nemanja; Subotić, Slobodan; Jakovljević, Mihajlo (Acta medicae Medianae, 2020)
The aim of this revision paper is to present the state of complementary and alternative medicine in the Republic of Serbia and compare it with other developing and developed countries around the world. In most countries of the world, the legalization and integration of the Complementary and Alternative Medicine (CAM) into the health system went very slowly until the 1970s, when there was an important global change in socio-economic conditions. WHO estimates that 83 billion was spent on traditional medicine in the world market in 2008. Significant variations in financial allocations to CAM across the globe have been observed, however, their direct comparison has been hampered by differences in the definitions and categorization of CAM used, as well as by the use of different currencies in different time periods. The development of CAM in the Balkans, during the 1990s, was hampered by war and transition, and the resolution of CAM was delayed. For the first time, the law regulates the implementation of the CAM in Serbia in 2005 by Article 235 of the Health Care Act. In the Republic of Serbia, evidence of the extent of use of CAM methods is very modest, although worldwide research shows an accelerated upward trend in the use of CAM. Data presented represents a path to further development and better recognition of CAM methods by the Ministry of Health of the Republic of Serbia.